METHODICAL RECOMMENDATIONS FOR TEACHING ENGLISH IN PRIMARY GRADES - Marjona Berdieva Vahobovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Every state, every nation is strong not only with its land and ground natural resources, military power and production potential, but also, first of all, with its high culture and spirituality. Therefore, in order to raise a healthy and well-rounded generation in our republic, great works are being carried out in terms of the scale and scope of the fundamental renewal and reform of the education system. The multicultural and multilingual "landscape" of Uzbekistan is an effective basis for the development of a person's language competence. English language education or, in the words of N. Galskova, "Linguistic and cultural education" further expands the opportunities and boundaries of the young generation to receive, deliver and interact with new and useful information (information). This article provides information on the use of modern methods of teaching English in primary classes, improving and improving the quality of lessons, and methodological recommendations for teaching English.